Clinical Implications of the Transversus Abdominis Plane Block in Adults - Mark J. Young; Andrew W. Gorlin; Vicki E. Modest; Sadeq A. Quraishi (Anesthesiology Research and Practice)
The transversus abdominis plane (TAP) block is a relatively new regional anesthesia technique that provides analgesia to the parietal peritoneum as well as the skin and muscles of the anterior abdominal wall. It has a high margin of safety and is technically simple to perform, especially under ultrasound guidance. A growing body of evidence supports the use of TAP blocks for a variety of abdominal procedures, yet, widespread adoption of this therapeutic adjunct has been slow. In part, this may be related to the limited sources for anesthesiologists to develop an appreciation for its sound anatomical basis and the versatility of its clinical application. As such, we provide a brief historical perspective on the TAP block, describe relevant anatomy, review current techniques, discuss pharmacologic considerations, and summarize the existing literature regarding its clinical utility with an emphasis on recently published studies that have not been included in other systematic reviews or meta-analyses.